2023
DOI: 10.1371/journal.pone.0292863
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of phosphodiesterase-5 inhibitor use and Alzheimer’s disease and related dementias among male and female patients aged 65 years and older supporting the need for a phase III clinical trial

David S. Henry,
Richard G. Pellegrino

Abstract: Background Phosphodiesterase-5 inhibitors (PDE5i) have been evaluated as a novel treatment for Alzheimer’s disease and related dementias (ADRD), but two recent cohort studies have offered opposing conclusions. Methods We performed an unmatched case-control study using electronic medical records from a large healthcare system to evaluate the association of PDE5i use and ADRD in patients ≥65 years old. Results Odds of PDE5i exposure were 64.2%, 55.7%, and 54.0% lower in patients with ADRD than controls among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Several in vitro and pre-clinical studies have suggested that PDE5 inhibitors may offer protective effects against AD, Vascular dementia (VaD), and Lewy body dementia (LBD) (3). Additionally, three recent cohort studies have found that Sildenafil usage was associated with reduced risk of AD (4)(5)(6). However, despite efforts to minimise bias, these studies remain susceptible to inherent methodological limitations of observational research, such as reverse causality and residual confounding, which could account for the observed protective effects (7).…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro and pre-clinical studies have suggested that PDE5 inhibitors may offer protective effects against AD, Vascular dementia (VaD), and Lewy body dementia (LBD) (3). Additionally, three recent cohort studies have found that Sildenafil usage was associated with reduced risk of AD (4)(5)(6). However, despite efforts to minimise bias, these studies remain susceptible to inherent methodological limitations of observational research, such as reverse causality and residual confounding, which could account for the observed protective effects (7).…”
Section: Introductionmentioning
confidence: 99%